The Association between Presentation by EMS and EMS Prenotification with Receipt of Intravenous Tissue-Type Plasminogen Activator in a State Implementing Stroke Systems of Care. (3rd May 2020) - Nielsen, Victoria M.; DeJoie-Stanton, Claudine; Song, Glory; Christie, Anita; Guo, Jing; Zachrison, Kori Sauser
Abstract: Introduction: Collaboration between emergency medical services (EMS) and hospitals receiving stroke patients is critical to ensure prompt, effective treatment, and is a key component of the stroke systems of care (SSoC). The goal of our study was to evaluate the association between presentation by EMS and EMS prenotification with odds of receiving Tissue-type Plasminogen Activator (IV-tPA) in a state implementing SSoC while rigorously accounting for missing data. Methods: We utilized data from the Massachusetts Paul Coverdell Stroke Registry for this study, and analyzed adult patients presenting with ischemic stroke to Massachusetts Coverdell hospitals between 2016 and 2018. Patients with contraindications to IV-tPA were excluded. We used generalized estimating equations to assess associations between presentation by EMS, EMS prenotification, and receipt of IV-tPA. We also performed a sensitivity analysis using multiple imputation to assess the sensitivity of our findings to missing data. Results: We identified 9, 230 eligible patients with ischemic stroke during the study period. In multivariate complete case regressions, presentation by EMS and EMS prenotification were associated with statistically significant increased odds of receiving IV-tPA (odds ratio [OR] 1.52, 95% confidence interval [CI] 1.28-1.80, p -value < 0.01; OR 1.75, 95% CI 1.36-2.24, p -value < 0.01, respectively). Analysis of imputed data indicated level or stronger associations. Conclusion: Our analysis indicates that presentation by EMS and EMS prenotification are associated with increased odds of receiving IV-tPA in a state implementing the SSoC. Our results lend importance to the critical role of EMS in the SSoC. Future interventions should work to increase rates of prenotification by EMS and assess inequities in receipt of IV-tPA.